2022
DOI: 10.3889/oamjms.2022.8083
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Incident Stunting in Elementary School Children in Endemic Area Iodine Deficiency Disorders Enrekang Regency

Abstract: BACKGROUND: Stunting is a global health emergency, including in Indonesia. The prevalence of childhood stunting in 2019 in Enrekang amounted to 44.8%. Enrekang Regency is the area with the highest stunting and is an endemic area. Iodine Deficiency Disorder (IDD) is thought to be correlated with the incidence of stunting. AIM: This study aims to identify the determinants of stunting in elementary school children in IDDs endemic areas in the Enrekang Regency. METHODS: An observational analytic study with a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…Parents play an important role in shaping children's eating behavior through parenting and eating patterns (27). Our previous study found a significant relationship between children's diet and the incidence of stunting in Enrekang villages (p=0.049) (28). This finding is in line with a study in Banyumas that found a significant relationship between maternal parenting and stunting (5).…”
Section: The Relationship Between Childbirth Spacing and Stuntingsupporting
confidence: 84%
“…Parents play an important role in shaping children's eating behavior through parenting and eating patterns (27). Our previous study found a significant relationship between children's diet and the incidence of stunting in Enrekang villages (p=0.049) (28). This finding is in line with a study in Banyumas that found a significant relationship between maternal parenting and stunting (5).…”
Section: The Relationship Between Childbirth Spacing and Stuntingsupporting
confidence: 84%
“…Basic Health Research (2018) reported a national stunting prevalence of 30.8% (7). This report shows 1 in 3 Indonesian children under five are stunted (4). The latest report according to the Indonesian Nutritional Status Survey for 2019, 2021 and 2022 shows that the total stunting children under five in Indonesia are 27.7%, 24.4%, and 21.6% (8).…”
Section: Introductionmentioning
confidence: 95%
“…Globally, in 2019 it was reported that around 144 million children under five (21.3%) were stunted. Of the world's 144 million children under five who are stunted, more than half come from low-and middle-income countries and only a quarter come from low-income countries (4). Indonesia as a developing country is classified as a health factor including stunting (5), and including countries with the fifth largest contributor to stunting worldwide (6).…”
Section: Introductionmentioning
confidence: 99%
“…Of the world's 144 million children under five who are stunted, more than half are from low-and middle-income countries and only a quarter are from low-income countries. More than half of the world's stunted children live in Asia (54%) and more than a third (40%) live in Africa [5]. Poor nutrition in childhood hinders a child's physical and mental development, giving rise to a vicious cycle of intergenerational malnutrition [6].…”
Section: Introductionmentioning
confidence: 99%
“…Basic Health Research (2018) reported a national stunting prevalence of 30.8% [9]. This shows that 1 in 3 children under five are stunted [5]. Based on the Indonesian Nutritional Status Survey report for 2019, 2021 and 2022, the total stunting toddlers in Indonesia are 27.7%, 24.4%, and 21.6% respectively [10].…”
Section: Introductionmentioning
confidence: 99%